2018
DOI: 10.1111/1751-7915.13308
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungal community of Dysphania ambrosioides from two heavy metal‐contaminated sites: evaluated by culture‐dependent and culture‐independent approaches

Abstract: SummaryEndophytic fungal communities of Dysphania ambrosioides, a hyperaccumulator growing at two Pb‐Zn‐contaminated sites, were investigated through culture‐dependent and culture‐independent approaches. A total of 237 culturable endophytic fungi (EF) were isolated from 368 tissue (shoot and roots) segments, and the colonization rate (CR) ranged from 9.64% to 65.98%. The isolates were identified to 43 taxa based on morphological characteristics and rDNA ITS sequence analysis. Among them, 13 taxa (30.23%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Geographic region had no effect and season had only a small effect on endophyte communities. In contrast, region was a determinant factor influencing endophytic fungi in various tissues of different plant species, such as leaves of Ageratina altissima (Christian et al ), and roots and shoots of Dysphania ambrosioides (Parmar et al ). A possible reason could be differences in key endophyte communities between domesticated plants and wild plants.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic region had no effect and season had only a small effect on endophyte communities. In contrast, region was a determinant factor influencing endophytic fungi in various tissues of different plant species, such as leaves of Ageratina altissima (Christian et al ), and roots and shoots of Dysphania ambrosioides (Parmar et al ). A possible reason could be differences in key endophyte communities between domesticated plants and wild plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, endophyte identification studies in Pinus taeda , Vitis vinifera and Dysphania ambrosioides via HTS have resulted in greater species richness when compared to culture-dependent methods, and have revealed distinct clades. However, the same studies have further revealed the absence of certain easily culturable taxa in the endophytic community structure derived via culture-independent techniques (e.g., HTS) [ 168 , 169 , 170 ]. Fungal endophyte communities elucidated by HTS likely depend more on the DNA extraction method, primers, and the platform used for sequencing and analysis.…”
Section: Culture-independent Methodsmentioning
confidence: 99%
“…Currently we have no reliable information on the ratio of cultivable to uncultivable fungal endophytes, but environmental DNA surveys suggest that the diversity of species is far greater than the diversity of cultivated isolates (Wu B. et al, 2019 ). A study on the endophytic fungal community of Dysphania ambrosioides , found that almost 10 times more species can be identified by amplicon sequencing than can be isolated by cultivation (Parmar et al, 2018 ). In order to increase the number of cultivable species and study their biosynthetic potential, it is of utmost importance to improve cultivation and isolation procedures.…”
Section: Future Directions For Successful Secondary Metabolite Biopromentioning
confidence: 99%